ANALYZING THE VALIDITY OF THE ARABIC TEXTBOOK FOR GRADE TEN OF MADRASAH ALIYAH THROUGH WILLIAM F. MACKEY'S PERSPECTIVE | William F. Mackey تحليل صلاحية كتاب اللغة العربية للصف العاشر بالمدرسة العالية في ضوء منظور - Ittaqi Haitsumakunti; Isniyatun Niswah MZ (Universitas Islam Negeri Palopo, 2026)
This study aims to analyze the components and feasibility of the Arabic textbook for the tenth grade of Madrasah Aliyah published by the Ministry of Religious Affairs of the Republic of Indonesia based on William F. Mackey’s perspective. This research employed a descriptive qualitative approach with a library research design and was analyzed using the content analysis method. The analysis focused on four major aspects proposed by William F. Mackey, namely selection, gradation, presentation, and repetition. The findings revealed that the textbook contains relatively complete language learning components. In terms of selection, the materials were considered relevant to students’ competencies and communicative needs. In terms of gradation, the materials were systematically organized from simple forms to more complex ones. In the aspect of presentation, the textbook applied staging, demonstration, contextual procedures, and pictorial procedures quite well, although differential procedures and ostensive procedures were still limited. Meanwhile, the repetition aspect demonstrated the implementation of rote, incremental, variational, and operational repetition. Based on the findings, the Arabic textbook for the tenth grade can generally be considered appropriate for use as a teaching material at Madrasah Aliyah, as it fulfills most of the textbook feasibility principles proposed by William F. Mackey.هدفت هذه الدراسة إلى تحليل مكونات كتاب اللغة العربية للصف العاشر بالمدرسة الثانوية الإسلامية الصادر عن وزارة الشؤون الدينية في جمهورية إندونيسيا ومدى صلاحيته للاستخدام، وذلك من منظور وليام ف. ماكي. اعتمد البحث على المنهج الوصفي النوعي بتصميم البحث المكتبي، وتمّ تحليل البيانات باستخدام أسلوب تحليل المحتوى. وقد تمحور التحليل حول أربعة محاور رئيسية اقترحها وليام ف. ماكي، وهي: الاختيار، والتدرج، والعرض، والتكرار. وقد كشفت النتائج أن الكتاب المدرسي يحتوي على مكونات تعليمية للغة شبه متكاملة. فمن حيث الاختيار، اعتُبرت المواد ذات صلة بكفاءات الطلاب واحتياجاتهم التواصلية. ومن حيث التدرج، جاءت المواد منظمةً بصورة منهجية من الأشكال البسيطة إلى الأكثر تعقيدًا. أما من حيث العرض، فقد طبّق الكتاب أساليب التدرج المرحلي، والعرض التوضيحي، والإجراءات السياقية، والإجراءات البصرية بشكل جيد، وإن كانت الإجراءات التفاضلية والإجراءات الإيضاحية المباشرة لا تزال محدودة. وفيما يخص التكرار، فقد تجلّى تطبيق أنواعه الأربعة، وهي: التكرار الحفظي، والتكرار التراكمي، والتكرار التنويعي، والتكرار التطبيقي. وبناءً على هذه النتائج، يمكن القول بشكل عام إن كتاب اللغة العربية للصف العاشر مناسب للاستخدام كمادة تعليمية في المدرسة الثانوية الإسلامية، إذ يستوفي معظم مبادئ صلاحية الكتاب المدرسي التي اقترحها وليام ف. ماكي.